Analysis of multi-scale morphodynamic behavior of a high energy beach facing the Sea of Japan - Karunarathna, Harshinie U.; Masae, Hajime; Baba, Yasuyuki (Frontiers in Marine Science, 2015)
Monthly cross shore beach profiles measured at the Ogata Wave Observation pier located in Joetsu-Ogata Coast, Niigata Prefecture, Japan, was analysed to investigate multi-scale morphodynamic beach behaviour. The Ogata beach, facing the Sea of Japan, is subjected to high energy wave conditions with that has a strong winter/summer seasonal signature. The measured beach profiles at the beach show very significant variability where cross-shore movement of shoreline position and lowering of the beach at the location of measurements exceed 20 m and 4 m respectively. The shoreline position seems to follow the seasonal variability of incident wave climate where a correlation coefficient of 0.77 was found between monthly averaged incident significant wave height and the measured monthly shoreline position. During the summer months, the beach variability mostly concentrated to in the sub-tidal part of the profile, while a significant amount of upper beach change was observed during the winter months. The beach profile shape was found to rotate between three different beach states in time; (i) concave reflective profile; (ii) profile with sub-tidal berm; and (iii) gentle, dissipative profile. Empirical Orthogonal Function (EOF) analysis of the profiles show that the variability of beach profile shape is dominated by (a) upper shoreface steepening; (b) sub tidal berm development and dissipation; and (c) variability of the overall profile slope, which have some longer than seasonal cyclic signatures. Comparison of temporal EOFs with climate indices such as Southern Oscillation Index and Pacific Decadal Oscillation index shows notable some correlations between profile change and climatic variability in the region. The analysis also shows that the morphological variability of Joetsu-Ogata Coast has similarities and some distinct spatial and temporal differences to beaches of similar kind found elsewhere.